External cervical resorption: an analysis using cone beam and microfocus computed tomography and scanning electron microscopy. (7th May 2013) - Gunst, V.; Mavridou, A.; Huybrechts, B.; Van, G.; Bergmans, L.; Lambrechts, P.
Abstract Aim To provide a three‐dimensional representation of external cervical resorption (ECR) with microscopy, stereo microscopy, cone beam computed tomography (CT), microfocus CT and scanning electron microscopy (SEM). Summary External cervical resorption is an aggressive form of root resorption, leading to a loss of dental hard tissues. This is due to clastic action, activated by a damage of the covering cementum and stimulated probably by infection. Clinically, it is a challenging situation as it is characterized by a late symptomatology. This is due to the pericanalar protection from a resorption‐resistant sheet, composed of pre‐dentine and surrounding dentine. The clastic activity is often associated with an attempt to repair, seen by the formation of osteoid tissue. Key learning points Cone beam CT is extremely useful in the diagnoses and treatment planning of ECR. SEM analyses provide a better insight into the activity of osteoclasts. The root canal is surrounded by a layer of dentine that is resistant to resorption.